Supporting Social Innovation in Children: Developing a Game to Promote Health Eating - Ptakauskaite, Nora; Chueng-Nainby, Priscilla; Pain, Helen (Proceedings of the The 15th International Conference on Interaction Design and Children, 2016)
Two things often observed in children: (1) many do not eat a healthy diet and (2) they like playing video-games. Game-based learning has proven to be an effective method for attitude change, and thus has the potential to influence children's eating habits. This study looks at how, through a series of workshop activities, children themselves can inform the design of such games. Using a co-constructive approach, the study's format promotes creativity and control, enabling children to act as valuable informants for its design. Patterns emerging from the study show that children do indeed understand the concept of healthy eating. Future phases of this work will explore whether they understand how various foods affect their bodies. This information will then inform the design of a video-game that encourages healthy eating.
Keywords: Innovation sociale; Réservé UdeM; Santé